Gambaran Skrining Kesehatan Mental Gen Z dengan SRQ-29 - Saputra, Noki Irawan; Wulan, Winda Ratna; Rahmatsyah, Hadi; Ashari, Dedi Nurhasan; Virgiandita, Zesty; Indriany, Dini; Pragholapati, Andria (Universitas Airlangga, 2025)
Generation Z, as a group born between the mid-1990s and early 2010s, faces complex mental health challenges amidst rapid social, economic and technological changes. This study aimed to explore the mental health characteristics of Generation Z, with the majority of respondents aged 20-21 years old. The instrument used was the SRQ-29. The results showed a high prevalence of post-traumatic stress disorder (57.0%), neurotic symptoms (39.0%), and psychotic symptoms (30.5%), with a very low rate of drug use (0.1%). This suggests that Generation Z was vulnerable to mental health, hence, primary and secondary prevention efforts related to PTSD as well as psychotic and neurotic disorders specific to Gen Z need to be initiated.